Nommer les lieux de la crise des opioïdes à Boston : un enjeu politique - Elsa Vivant (EchoGéo)
This paper analyses the different toponyms of an open drug use scene in Boston, located at the interface of three neighborhoods with contrasting uses and dynamics. The reactions and demands of the residents of these different neighbourhoods reveal the power relationships in the urban space, the toponymic choices of which are the main focus of the analysis: Mass & Cass refers to the urban, colonial and racial history of the city and prohibition; Methadone Mile recalls the stigmatisation of users and places of care; Recovery Road expresses the emergence of new care and harm reduction practices at work in this sector. Entering this scene by name helps to unravel the complexity of the opioid crisis currently underway in the USA, the political stakes involved and the changes it is driving in drug policy.